Unbalanced images and inappropriate responses : how three Western newspapers misrepresented the 1992-3 Somalian famine : a thesis presented in [partial] fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Hope, James Nicholas (Massey University, 1996)
There is widespread agreement among media analysts that the media in capitalist societies, such as Australia, New Zealand, the United States and the United Kingdom, present "news" in particular ways which favour certain readings of events over others. Whether this is an explicit or implicit act is open to debate. Regardless, the portrayal of events in the developing world, such as the tragic famine in Somalia in 1992-3, are not quarantined from this process. Consequently, the images of the developing world created in the West by the mainstream media are often highly distorted. This situation has serious ramifications as it is influential in determining the type and extent of development considered appropriate by the West for the developing world, and the assistance and aid provided. If Western understanding of the events and issues in the developing world is based on the one-sided images transmitted by the media, then this knowledge is incomplete and decisions taken on the basis of this knowledge will not meet the needs of the societies concerned. Therefore, it is not surprising that the history of Western aid for the developing world has been one of incompetence, errors and inappropriate responses. This thesis provides a critical insight into how and why the Western media works explicitly to shape the "news" we see by analysing how three newspapers, two from the United Kingdom and one from the United States, presented their coverage of the 1992-3 Somalian famine. This analysis, it is hoped, will deepen the reader's understanding of the role of the media in development matters, will alert the reader to the need to adopt a critical approach to media treatment of these matters and will provide the reader with knowledge and resources to assist in the development of such an approach. The adoption of a critical approach to media stereotyping and manipulation will be beneficial in that it will lead to a better understanding of developing world societies and more meaningful interaction between these societies and the West.
Keywords: Somalia; Famines; Food relief; Press coverage